The effect of physical exercise on vital lung capacity in Tapak Suci athletes - Sukadiono Sukadiono; Siti Fatimatus Zahrah; Dede Nasrullah; Supatmi Supatmi; Vika Ramadhana Fitriyani (Jurnal Keolahragaan, 2022)
Exercise can have a physiological effect on the body, including the work system of the heart and lungs. The lungs have an important role in human life, where there is an exchange of oxygen with carbon dioxide through the respiratory process. In terms of health, exercise needs to be done by every human being, because exercise can increase the work of the lung muscles, whereas if the lung muscles work well, the ability to accommodate oxygen or the vital capacity of the human lungs also increases. The purpose of this study was to determine the effect of physical exercise on vital lung capacity. This research method uses a pre-experimental approach with pre and post-test one-group design. The sampling technique of this study used a random sampling of 30 respondents. The instruments used were observation sheets from the examination of vital lung capacity and spirometry. Analysis Research data analysis using the Wilcoxon Rank Test. The results of the Wilcoxon Rank Test statistical test obtained P = 0.000 with a safety level of = 0.05 meaning P value = . Conclusion It can be concluded that there is a difference in the vital capacity of the lungs before and after participating in the sacred tapak exercise so that this research is expected to be useful for athletics in improving physical fitness, especially by routinely doing sports or physical exercise such as participating in the sacred tapak exercise.